Study of the Influence of Turbulence Models on Hydrodynamic and Thermal Parameters of Heat Carriers in Calculations of Heat Exchangers - Zhumanbayeva, A.S.; Jaichibekov, N.Zh.; Kurmanova, D.Y. (Bulletin of the Karaganda University. “Physics” Series., 2025)
In this paper, the heat exchange processes between a cold (oil) and a highly heated (water) heat carrier in a “tube-in-tube” type heat exchanger with a parallel flow scheme are studied using semi-empirical turbulence models: k-ω SST, k-ε, and Transition SST. The analysis of the obtained results showed that the k-ω SST turbulence model was more preferable for the calculation of a heat exchanger with a sufficiently small tube diameter, because of the effect of the boundary layer in the tube. This turbulence model more pronouncedly reproduces the laminar-turbulent transition, which is carried out in these processes, where the viscosity of oil strongly depends on temperature. Finite difference and finite volume methods were chosen for numerical modelling and calculation of heat exchange processes. The calculations were carried out on the basis of Computational Fluid Dynamics, using the Ansys Fluent. The RANS equations closed by means of the gamma-Retheta turbulence model, which takes into account the laminar-turbulent transition and the k-ω SST model equations, were used for numerical modelling of coolant hydrodynamics. Based on the proposed turbulence model, the distributions of hydrodynamic and thermal parameters and similarity criteria (Re, Pr, Nu) of the process along the length of the tube are obtained.
Keywords: heat transfer; numerical calculation; heat exchanger; oil; hydrodynamics; cooling fluids; heat flow; laminar-turbulent transition; intermittency; heat exchange intensity; viscosity